Sexual Well-Being in Adult Male Patients with Congenital Adrenal Hyperplasia - Bogna Dudzińska; Jonas Leubner; Manfred Ventz; Marcus Quinkler (International Journal of Endocrinology, 2014)
Introduction. Men with congenital adrenal hyperplasia (CAH) due to 21-hydroxylase deficiency show impaired fecundity due to testicular adrenal rest tumors and/or suppression of the gonadal axis. Sexual well-being might be an additional factor; however, no data exists. Patients and Methods. Prospective longitudinal monocentric study included 20 male CAH patients (14 salt wasting, 6 simple virilizing; age 18–49 yr). Clinical assessment, testicular ultrasound, biochemical and hormonal parameters, three validated self-assessment questionnaires (SF-36, GBB-24, and HADS), and male Brief Sexual Function Inventory (BSFI) were analyzed at baseline and after two years. Results. Basal LH and testosterone levels suggested normal testicular function. LH and FSH responses to GnRH were more pronounced in patients with a good therapy control according to androstenedione/testosterone ratio < 0.2. This group had significant higher percentage of patients on dexamethasone medication. GBB-24, HADS, and SF-36 showed impaired z-scores and no changes at follow-up. BSFI revealed impairments in dimensions “sexual drive,” “erections,” and “ejaculations,” whereas “problem assessment” and “overall satisfaction” revealed normal z-scores. Androstenedione levels correlated (P=0.036) inversely with z-scores for “sexual drive” with higher levels associated with impaired “sexual drive.” Conclusion. Male CAH patients showed a partly impaired sexual well-being which might be an additional factor for reduced fecundity.